Collaboration Skill of Students by Problem Based Learning Model - Sedyati, Retna Ngesti; Herlindawati, Dwi; Rachmawati, Sela (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The aplication of the problem based learning model in accounting computer learning can train students’ collaboration skill. Especially in accounting computer learning requires the ability to analyze transactions and process data to be used as financial report. So collaboration skill are needed in learning process. This quantitative descriptive research aims to describe students’ collaborations skill trough problem based learning models. The sample of this study was 137 Student taken using a total sampling technique. The research instrument used are observations, interviews, and documents. Analysis data used percentage analysis and interpreted according to categorization and explained with descriptive form. The result of the study show that collaboration skill are included in the high category. However, of the five aspects of collaboration skills that were measured. There was a low aspect namely investigation technique aspect. This is because students are less active in utilizing available learning resources. Such as using libraries and the internet as learning resource to find detailed information.